B cell depletion and signs of sepsis-acquired immunodeficiency in bone marrow and spleen of COVID-19 deceased. (February 2021) - Ihlow, Jana; Michaelis, Edward; Greuel, Selina; Heynol, Verena; Lehmann, Annika; Radbruch, Helena; Meinhardt, Jenny; Miller, Florian; Herbst, Hermann; Corman, Victor Max; Westermann, Jörg; Bullinger, Lars; et al.
Highlights: Lymphocytopenia in COVID-19 decedents is accompanied by B cell depletion in bone marrow and spleen. COVID-19 decedents with B cell loss show a tendency towards higher pulmonary SARS-CoV-2 burden. Loss of B cells and plasma cells may impede the humoral immune response to SARS-CoV-2. COVID-19 decedents show signs of sepsis-induced immunodeficiency in the bone marrow. Abstract: Objectives: In coronavirus disease 2019 (COVID-19), the adaptive immune response is of considerable importance, and detailed cellular immune reactions in the hematological system of patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are yet to be clarified. Methods: This study reports the morphological characterization of both bone marrow and spleen in 11 COVID-19 decedents with respect to findings in the peripheral blood and pulmonary SARS-CoV-2 burden. Results: In the bone marrow, activation and left shift were found in at least 55% of patients, which was mirrored by peripheral anaemia, granulocytic immaturity and multiple thromboembolic events. Signs of sepsis-acquired immunodeficiency were found in the setting of an abscess-forming superinfection of viral COVID-19 pneumonia. Furthermore, a severe B cell loss was observed in the bone marrow and/or spleen in 64% of COVID-19 patients. This was reflected by lymphocytopenia in the peripheral blood. As compared to B cell preservation, B cell loss was associated with a higher pulmonary SARS-CoV-2 burden and only a marginal decrease of of T cell counts. Conclusions: The results of this study suggest the presence of sepsis-related immunodeficiency in severe COVID-19 pneumonia with superinfection. Furthermore, our findings indicate that lymphocytopenia in COVID-19 is accompanied by B cell depletion in hematopoietic tissue, which might impede the durability of the humoral immune response to SARS-CoV-2.